From Reformist to Hermeneutics: A Genealogy of Interpretationin the Modern-Contemporary Periods - Mokh. Fatkhur Rokhman; Abdul Kadir Riyadi (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The transformation of Qur’anic interpretation in the modern and contemporary periods represents one of the most significant epistemological shifts in modern Islamic intellectual history. Nevertheless, existing scholarship has predominantly examined this transformation through descriptive, thematic, or biographical approaches, often overlooking the deeper relations between interpretation, discourse, power, and the historical construction of religious authority. This study aims to critically investigate the genealogy of Qur’anic interpretation from reformist exegesis to contemporary hermeneutics through Michel Foucault’s genealogical framework. Employing a qualitative critical-textual design, the research analyzes major interpretive and theoretical works of influential Muslim thinkers, including Muhammad Abduh, Rashid Riḍā, Fazlur Rahman, Nasr Hamid Abu Zayd, and Mohammed Arkoun. Data were examined using genealogical analysis and critical discourse analysis to identify epistemological ruptures, discursive transformations, and shifts in interpretive legitimacy across different historical periods. The findings demonstrate that the transition from reformist tafsir to contemporary hermeneutics did not emerge as a linear methodological evolution, but as a historically contingent epistemological rupture shaped by colonialism, modernization, globalization, and the encounter between Islamic scholarship and modern critical humanities. Reformist interpretation reconstructed the Qur’an as a rational and socially transformative discourse, whereas contemporary hermeneutics repositioned interpretation as a historically conditioned, discursively negotiated, and contextually produced process of meaning-making. The study further reveals that contemporary tafsir increasingly integrates interdisciplinary approaches emphasizing historicity, plurality, and critical reflexivity, thereby destabilizing singular structures of interpretive authority within modern Muslim societies. Theoretically, this research reconceptualizes Qur’anic interpretation not as a fixed theological tradition, but as a dynamic discursive formation continuously shaped by struggles over knowledge, legitimacy, and socio-political power, thereby contributing a critical genealogical perspective to contemporary global debates in Qur’anic studies and Islamic hermeneutics.